Factors of the formation of cinematographic art and artistic evolution - Iqbal Mamasodikovich Melikuziev (Zien Journals, 2023)
This scientific article is devoted to the history of Uzbek cinematography, feature films and documentaries created in the early years of its existence, their artistic quality, the operator creates these films using a camera and lens, transmits to the viewer the idea of the screenwriter, artist, director and the physiological state of the actor. At the same time, the article expresses scientifically grounded opinions on the importance of Uzbek cinematography for the development of Uzbek cinema
Keywords: Cinematography; art; history; Object